The Synonymy of the Toxic Dinoflagellates Prorocentrum mexicanum and P. rhathymum and the Description of P. steidingerae sp. nov. (Prorocentrales, Dinophyceae). (10th March 2017) - Gómez, Fernando; Qiu, Dajun; Lin, Senjie
Abstract: Prorocentrum mexicanum and P. rhathymum are toxicologically important dinoflagellates, but their relationship is not well defined. We investigated strains from Puerto Rico and Brazil by light and scanning electron microscopies. We provide molecular data from a strain isolated near the type locality of P. rhathymum, and the first morphological and molecular data from the South Atlantic Ocean. The rRNA gene (rDNA) sequences of the Puerto Rican and Brazilian strains were identical, and their morphologies fit the description of P . rhathymum . In the molecular phylogenies, the globally distributed populations under the names P. mexicanum and P . rhathymum are intermixed and branched together, except for several divergent strains from Florida and Cuba. We examined the original descriptions and iconotypes of the species Prorocentrum maximum, P. brochii, P. mexicanum, and P. rhathymum . We conclude that P. maximum sensu Schiller's figure 41a corresponds to the earlier description of this species; the split of P. mexicanum and P. rhathymum was based on a misidentification because P. mexicanum sensu Cortés‐Altamirano & Sierra‐Beltrán corresponds to P. texanum var. cuspidatum ; and P. rhathymum is a junior synonym of P. mexicanum . Several Floridian and Cuban strains correspond to a new species, which we describe as Prorocentrum steidingerae sp. nov.